?! - Henriette Stange; Aleksej Lissitsa (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2004)
" " . , , : , . , 1993 2000 . (Data Envelopment Analysis (D)) , - D , . 1993 373, 2000 - 367 , . D 2000 , 1993 . , , . , 1993 2000 . – – This Discussion Paper has been occupied with the analysis of the technical and scale efficiency of Russian farms during the transformation process. Especially the influence of the factors farm size, legal form and specialization is analysed. In order to list the effects of reforms and the changes in farms, the observation years 1993 and 2000 are compared. As a methodical instru-ment has been chosen an input-oriented model of Data Envelopment Analysis (DEA) for efficiency measurement as well as the DEA-Superefficiency model for identification of outliers and inspection of data stability. We analysed in year 1993 373 and the year of 2000 367 successors of former kolkhozes and state farms in Oblast Moscow. The results of the DEA model calculations show an improvement in average efficiency from 1993 to 2000. In consideration of the performance-influencing factors to technical efficiency, the choice of the legal form does not have any influence. On the other hand farm size and specialization influence the technical and scale efficiency in both years.
urn:nbn:de:gbv:3:2-22516
Keywords: Q12; D2; O1; O4; P3; 330; Effizienz; Supereffizienz; Data Envelopment Analysis; Transformationsprozess; Russland